Curculigoside rescues hippocampal synaptic deficits elicited by PTSD through activating cAMP‐PKA signaling. (6th October 2022) - Ji, Manman; Zhang, Zhengrong; Gao, Feng; Yang, Shaojie; Wang, Juan; Wang, Xuncui; Zhu, Guoqi
Abstract: Chronic traumatic stress results in various psychiatric disorders, especially posttraumatic stress disorder (PTSD). Previous study demonstrated that curculigoside (CUR) a component of Rhizoma Curculiginis prevented fear extinction and stress‐induced depression‐like behaviors. However, its effects on PTSD and the mechanisms are still not completely clear. In this study, we observed typical PTSD‐like phenotypes, synaptic deficit, and reduction of BDNF/TrkB signaling pathway in mice receiving modified single prolonged stress and electrical stimulation (SPS&S). By contrast, systemic administration of CUR blocked PTSD‐like phenotypes and synaptic deficits, including reduction of BDNF/TrkB signaling pathway, GluA1 and Arc expression. Importantly, CUR reversed the impairment of PKA signaling pathway elicited by PTSD. We further confirmed that the effects of CUR on synaptic function were through PKA signaling pathway, as H‐89, an inhibitor of PKA blocked the effect of CUR on behavioral changes and BDNF/TrkB signaling pathway. Thereafter, we verified that CUR on synaptic function were through PKA pathway using direct intracerebral injection of CUR and H‐89. Direct intracerebral injection of CUR activated PKA/CREB/BDNF/TrkB, which was blocked by H‐89. Additionally, the docking results showed high binding energies of CUR with A2AR, AC, PRKACA, and PRKAR1A, which might indicate that CUR functions through regulating PKA signaling pathway. In conclusion, CUR prevented the behavioral changes and hippocampal synaptic deficits elicited by PTSD through activating cAMP‐PKA signaling.